Sosialisasi Bahaya Kosmetik Bagi Masyarakat Desa Bingkat Kecamatan Pegajahan Kabupaten Serdang Bedagai - Enny Fitriani; Lili Nurmaliza; Rhina Chairani; Ananda Pan Achmad; Dicky Nizar Dermawan; Kamelia; Maulida Sari (STIKES Columbia Asia Medan, 2025)
Cosmetic use is increasing among residents of Bingkat Village, but many still lack awareness of safe usage practices. This issue is worsened by the circulation of illegal cosmetics and limited knowledge about harmful ingredients. The aim of this activity was to educate the community on proper ways to obtain, use, store, and dispose of cosmetics. The method involved direct counseling and training at the village hall by lecturers and students of STIKes Indah Medan using a participatory approach. The program began with a presentation, followed by a question-and-answer session and practical training to recognize safe products. The results showed improved community understanding, as reflected in participants’ enthusiasm during discussions and their ability to distinguish between safe and risky cosmetic products. The program also provided students with valuable field experience in health education. In conclusion, educating the public about safe cosmetics contributes to increased awareness and encourages responsible cosmetic use to support skin health.